Potential role for Stylo in traditional crop and livestock production systems in the Nigerian subhumid zone - Mohamed-Saleem, M.A.; Kaufmann, Ralph R. von; Otsyina, R.M.; Suleiman, H. (Science Council of Japan, 1985)
Discusses some methods of growing cereal Crops in association with Stylosanthes in traditional Crop-livestock production systems in the subhumid zone of Nigeria. Examines effects of undersowing Stylo on sorghum yield and total fodder; land preparation on grain & fodder production; land history on soil properties & maize response; and change in Crop geometry on grain & fodder yields.